(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The modern education system is experiencing rapid transformations due to globalization and technological advancements. One of the key challenges in this process is ensuring the effectiveness of teaching by incorporating innovative and interactive learning approaches. The synergetic approach, originally developed in natural sciences, has been increasingly applied in pedagogy, offering a holistic and systematic perspective on the educational process. In Uzbekistan, educational reforms are actively integrating modern pedagogical technologies to enhance learning outcomes. This study examines the role of the synergetic approach in improving educational quality, fostering students’ independent thinking, and developing teachers’ organizational competencies. Through a comprehensive review of scientific literature, international best practices, and empirical data, this research highlights the potential benefits of synergetic pedagogy in optimizing the teaching and learning process. Additionally, practical recommendations for implementing this approach in Uzbekistan’s education system are provided, focusing on enhancing interactive learning environments, professional development for educators, and strategies to strengthen students’ engagement. The findings of this study contribute to the ongoing discourse on educational innovation and offer insights for policymakers, educators, and researchers in the field of pedagogy.